Experimental Research on Mix Ratio of Construction Waste Cemented Filling Material Based on Response Surface Methodology - Weixin Chen; Guohua Zhang; Qin Tao; Liangliang Yu; Tao Li; Xianhua Guan (Advances in Materials Science and Engineering)
In order to solve the problem of insufficient supply of aggregate for cemented filling material, the experimental research on the mix ratio of cemented filling material using construction waste as recycled coarse aggregate was carried out. A ternary quadratic regression model was created using the Box-Behnken design (BBD) based on the response surface methodology (RSM), using slump, bleeding ratio, and 28 d uniaxial compressive strength of the filling material as response variables, and the model’s accuracy and reliability were confirmed. The findings of the regression model reveal that the response value is influenced by a single component as well as the interaction between the two factors. Finally, based on filling material cost optimization model, an optimal mix ratio is given, in which the wet fly ash/aggregate ratio, Talbol gradation index of recycled aggregate, and dosage of water reducing agent to cement are 0.507, 0.5, and 0.678%, respectively. The filling material which adopted the optimal mix ratio exhibited a good performance with slump of 215 mm and bleeding ratio of 4.00%, uniaxial compressive strength increased significantly within 3 d, and 28 d uniaxial compressive strength was 4.08 MPa, which meet the requirements of field construction.